PENGARUH RASIO PROFITABILITAS, SOLVABILITAS DAN LIKUIDITAS TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN CONSUMER GOODS DI BEI (PERIODE 2016-2018) - Mursila Hanum; Febriyanto Febriyanto; Ardiansyah Japlani (Derivatif : Jurnal Manajemen, 2020)
This study aims to determine the influence found in financial ratios with dividend policy. Namely (1) profitability ratio (ROE), (2) solvency ratio (DER), (3) liquidity ratio (CR) with (4) dividend policy (DPR). The object of this research is consumer goods companies listed on the Indonesia Stock Exchange during the period of 2016 to 2018. The population in this study were 52 companies that were officially listed on the Indonesia Stock Exchange. The sampling technique used is purposive sampling. So as to obtain a sample of 30 companies that meet the required sample characteristics. This study uses a quantitative approach, data were analyzed using the IBM SPSS Statistics 21 software. The results showed that only the profitabi;ity ratio had a significant influence with the dividend policy, financial ratio variables ( 1.solvency ratio 2.likuidity ratio) had no influence with the policy dividend. Keywords: Profitability Ratio (ROE), Solvency Ratio (DER), Liquidity Ratio (CR), Dividend Policy (DPR)